The evaluation of the Article 15zzs1 Section 1 Point 4 of the Anti-Covid Act from the perspective of the principle of citizens’ participation in the administration of justice (Discourse of Law and Administration, 2022)
The article discusess the impact of anti-Covid-19 regulations on the principle of citizens’participation in the administration of justice. Through analysing this topic it is proven that this principle plays a key role in assuring parties the right to proper and independent court. Therefore, the exclusion of this principle in civil proceedings under the Article 15zzs1 Section 1 Point 4 of the Anti-Covid Act, although legally permissible, has not been properly justified by the Polish legislator. On the contrary, the possibility of conducting remote hearings alongside the fact that this limitation was introduced only in relation to civil cases leads to the conclusion that there are no axiological grounds for such changes. As a consequence, the article calls for the necessity to repeal this regulation and return to the previously binding provisions which fully respected the principle of citizens’ participation in the administration of justice.
Keywords: court composition; collegiality rule; individuality of the court panel; lay judges; COVID-19 pandemic; the principle of citizens’participation in the administration of justice